2015
DOI: 10.22329/il.v35i1.4209
|View full text |Cite
|
Sign up to set email alerts
|

Bogency and Goodacies: On Argument Quality in Virtue Argumentation Theory

Abstract: Virtue argumentation theory (VAT) has been charged of being incomplete, given its alleged inability to account for argument cogency in virtue-theoretical terms. Instead of defending VAT against that challenge, I suggest it is misplaced, since it is based on a premise VAT does not endorse, and raises an issue that most versions of VAT need not consider problematic. This in turn allows distinguishing several varieties of VAT, and clarifying what really matters for them. Résumé:On a reproché à la théorie des vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…It also explains the close focus on the ad hominem fallacy, which is conspicuous in many accounts of the relation of the virtues to argumentation theory, as discussed further below (Johnson 2009;Battaly 2010;Jason 2011;Bowell and Kingsbury 2013;Aberdein 2014;Bondy 2015;Leibowitz 2016). More recently, it has been suggested that an undue focus on ad hominem may distract from virtue argumentation theory's strengths-and from some of its other problems (Paglieri 2015). The latter include the 'incompleteness problem', of explaining why virtues are worthwhile (MacPherson 2014); the question of whether there are virtues specific to argumentation (Goddu 2015); and the issue of how (or whether) the conflict of virtues may be resolved.…”
Section: Rootsmentioning
confidence: 92%
See 1 more Smart Citation
“…It also explains the close focus on the ad hominem fallacy, which is conspicuous in many accounts of the relation of the virtues to argumentation theory, as discussed further below (Johnson 2009;Battaly 2010;Jason 2011;Bowell and Kingsbury 2013;Aberdein 2014;Bondy 2015;Leibowitz 2016). More recently, it has been suggested that an undue focus on ad hominem may distract from virtue argumentation theory's strengths-and from some of its other problems (Paglieri 2015). The latter include the 'incompleteness problem', of explaining why virtues are worthwhile (MacPherson 2014); the question of whether there are virtues specific to argumentation (Goddu 2015); and the issue of how (or whether) the conflict of virtues may be resolved.…”
Section: Rootsmentioning
confidence: 92%
“…In particular, most virtue argumentation theorists recognize open-mindedness as an important virtue (Cohen 2009), thereby building on a substantial body of recent work in virtue epistemology (Riggs 2010;Baehr 2011;Tiberius 2012) and the philosophy of education (Hare 1985(Hare , 2003(Hare , 2009Hare and McLaughlin 1998;Higgins 2009;Siegel 2009). Lastly, the virtue argumentation programme is now sufficiently mature to have produced overviews, whether positive (Cohen 2013b;Aberdein 2014), negative (Bowell and Kingsbury 2013;Bondy 2015), or studiously even-handed (Paglieri 2015).…”
Section: Rootsmentioning
confidence: 99%
“…So, in evaluating people's arguments, we need to consider, as far as we are able, the sorts of virtues or vices that people are exemplifying in giving their arguments. Intellectual virtues are traits which involve being disposed to form true 1 Paglieri (2015) also aims to pull apart discussions of virtue argumentation theory and ad hominem arguments, though for a different reason: whereas I argue that virtue argumentation theory doesn't offer a better account of ad hominem arguments than an evidentialist approach does, Paglieri thinks that the discussion of ad hominems is a bit of a red herring for virtue theory in the first place.…”
Section: Ad Hominems and Virtue Epistemologymentioning
confidence: 99%
“…However, there is a second, and perhaps more important, reason people have opted for a virtue-theoretic construal of argument goodness. The reason is that, if we think that what makes arguments good is that they are cogent, in the sense that they satisfy the RSA criteria (relevance, sufficiency, acceptability), then we will be faced with the kind of serious intuitive counterexamples which Paglieri (2015) calls "bogent" (bad but cogent) arguments. Paglieri borrows two examples from Cohen (2013), where Cohen is voicing some deep dissatisfaction with the notion that cogency is sufficient for good argument.…”
mentioning
confidence: 99%
“…Bowell and Kingsbury (2013) have warned against using traits of the arguer as the basis for argument appraisal, while Aberdein (2010Aberdein ( , 2014 has argued that it can be done and can actually be a fruitful methodology. Fabio Paglieri (2015) offers an insightful analysis of this discussion, and claims that one of the benefits of virtue argumentation theory could precisely be the adoption of a broader conception of argument than that of informal logic. This is one of the paths that I will pursue in this article.…”
Section: Puts Itmentioning
confidence: 99%